Installation systems of on-site prefabricated concrete components: a qualitative approach - Hanafi, Mohd Hanizun; Farrell, Peter; Yusoff, Mohd Nazaruddin; Abdullah, Shardy; Razak, Arman Abdul (2017)
The construction industry has been identified as one of the more important sectors towards realizing the aim of making Malaysia a developed country by the year 2020. Towards this end, the construction industry needs to become more competitive and productive. One major strategy is the implementation of the industrialized building system (IBS). The implementation of IBS requires comprehensive studies to be undertaken to allow project stakeholders fully understand the benefits that may be gained from IBS. The selection of an appropriate installation system is vital in making IBS effective and successful. This paper identifies the on-site prefabricated component installation systems practised and appraises the factors for selection. Structured interviews were carried out with 32 parties directly involved in the on-site prefabricated components installation operation. The study reveals three main prefabricated component installation systems, namely the horizontal-, vertical- and mixed-based systems. Six main influencing factors were also discovered that allow for a more informed decision to be made on system selection. Out of the six factors, it was revealed that the availability of prefabricated components and crane mobility to be the most important factors in determining installation system selection.